1996
DOI: 10.1063/1.868818
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the capillary instability in the Rayleigh–Taylor slot problem

Abstract: Stability of capillary-gravity interfacial waves between two bounded fluidsThe classical Rayleigh-Taylor instability for an interface of finite extent is modified by two independently controlled perturbation effects. A component of gravitational acceleration tangent to the interface is imposed and the interface is subjected to a flow-induced pressure field. The stability of the flat horizontal interface when surface tension holds heavier liquid above ambient gas is considered in a 2D model problem. The two per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The codimension-2 nature of the subcritical pitchfork gives an additional independent control parameter and thus provides access to a greater range of nonlinear behaviour. We remark that this nonlinear stabilization concept has also been predicted for the Rayleigh-Taylor instability in two contexts: a two-dimensional slot (Chen & Steen 1996a) and a Hele-Shaw thermal cell (Chen & Steen 1996b). In both cases, tilt angle and flow-induced pressures are the competing perturbations.…”
Section: Discussionsupporting
confidence: 58%
“…The codimension-2 nature of the subcritical pitchfork gives an additional independent control parameter and thus provides access to a greater range of nonlinear behaviour. We remark that this nonlinear stabilization concept has also been predicted for the Rayleigh-Taylor instability in two contexts: a two-dimensional slot (Chen & Steen 1996a) and a Hele-Shaw thermal cell (Chen & Steen 1996b). In both cases, tilt angle and flow-induced pressures are the competing perturbations.…”
Section: Discussionsupporting
confidence: 58%
“…However, numerical search for blow-up behaviour is extremely tedious and an analytical estimate of its existence would be most convenient. Oron & Rosenau (1989) and Chen & Steen (1996) examined the existence of saturated small-amplitude solutions to the lubrication equations and use that as a sufficient condition for blow-up not to occur -their non-existence is a necessary condition for blow-up. Their saturated solutions are assumed to be either spatially periodic or confined to a finite box to simplify the bifurcation analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Stabilization by evaporation has been demonstrated by Schubert and Straus 2 and by Adham-Khodaparast 3 et al; stabilization by combining two imperfections has been shown by Chen and Steen. 4 Rasenat 5 et al have shown that a stable density difference across a surface can stabilize two layers which, on average, are RayleighÀTaylor unstable.…”
Section: Introductionmentioning
confidence: 99%